Digital contact tracing during the COVID-19 pandemic in France: Associated factors and reasons for non-use. (March 2023) - Touzani, Rajae; Schultz, Emilien; Vandentorren, Stéphanie; Arwidson, Pierre; Guillemin, Francis; Bouhnik, Anne-Déborah; Rouquette, Alexandra; Mancini, Julien
Highlights: In France, at the start of 2021, the proportion of those who declare that they have never downloaded the TousAntiCovid application remains quite high (63.3%). Financial deprivation is associated with never downloading the app. The fear of using personal data is one of the reasons for not using contact tracing. Abstract: Objectives: To estimate the proportion of users of the TousAntiCovid app(lication) and identify factors associated with its non-use for contact tracing. Methods: We conducted an online survey of a quota sample of French adults between 8 and 18 January 2021. Three categories of TousAntiCovid use were considered: contact tracing, other or temporary usage, and no use. A weighted multiple logistic regression was performed to analyze the factors associated with these different uses. Results: Among the 1 000 respondents, 63.3% declared they had never downloaded the TousAntiCovid app, 23.5% used it for contact tracing. The remaining 13.2% did not enable contact tracing, mainly because of excessive battery consumption and fear of misuse of personal data. Trust in political representatives, financial deprivation and other factors were associated with never downloading the app. Conclusion: This study confirms the previously suggested links between trust in political representatives, financial deprivation and the use of contact tracing apps in France.